The effect of Pilates exercises at different levels in the development of some motor abilities and their relationship to the accuracy of passing football skill performance (Journal of the College of Basic Education, 2022)
Scientific progress witnessed new boundless horizons in sports sciences, including the science of sports training, and these sciences were harnessed to serve sports performance because of their well-established principles and rules on which to base and derive their material. There is no doubt that sports training has general rules, as researchers followed them in developing sports performance in contexts Appropriate and correct was in the service of society. Today, everyone seeks to achieve sporting achievements by keeping up with the latest training methods used to develop the level of sports performance. Hence, the importance of plate exercises is evident, as it is a group of physical movements designed to strengthen the body and achieve its balance, accompanied by patterns of focused breathing, and its effect is not limited to achieving agility and strength only, but also extends to rehabilitating the body in all respects, in addition to the fact that movement abilities are of great importance in most activities And sporting events, including a game in football, which contributes effectively to developing the accuracy of football skills, including passing skill.Hence the importance of the research on the theoretical side, since the research deals with a new topic in the science of training and sports learning. From the scientific side, the research is an addition in the field of serving the football game by finding the best curricula and means for training and education.